2022
DOI: 10.3390/ijms232214482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mitochondrial Alterations in Aicardi–Goutières Patients Mutated in RNASEH2A and RNASEH2B Genes

Abstract: Aicardi–Goutières syndrome (AGS) is a rare encephalopathy characterized by neurological and immunological features. Mitochondrial dysfunctions may lead to mitochondrial DNA (mtDNA) release and consequent immune system activation. We investigated the role of mitochondria and mtDNA in AGS pathogenesis by studying patients mutated in RNASEH2B and RNASEH2A genes. Lymphoblastoid cell lines (LCLs) from RNASEH2A- and RNASEH2B-mutated patients and healthy control were used. Transmission Electron Microscopy (TEM) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
3
4
0
Order By: Relevance
“…These differences were associated prevalently with the RNASEH2B mutations, the most commonly altered gene in the pathology ( 4 , 5 ). These results are in accordance with our previously published data which underlined an increase in the mtDNA copy number particularly in RNASEH2B -mutated LCLs ( 30 ), but further investigations are needed to better understand how the mtDNA methylation influences the mtDNA copy number increase. Nothing was previously established or described in the literature in relation to this condition, so we explored this feature as well as the pattern of methylation in mtDNA for the first time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These differences were associated prevalently with the RNASEH2B mutations, the most commonly altered gene in the pathology ( 4 , 5 ). These results are in accordance with our previously published data which underlined an increase in the mtDNA copy number particularly in RNASEH2B -mutated LCLs ( 30 ), but further investigations are needed to better understand how the mtDNA methylation influences the mtDNA copy number increase. Nothing was previously established or described in the literature in relation to this condition, so we explored this feature as well as the pattern of methylation in mtDNA for the first time.…”
Section: Discussionsupporting
confidence: 92%
“…According to our hypothesis, the amount of mtDNA may be higher in AGS patients and may be released from the abnormal mitochondria, activating immune systems, and producing the elevated levels of IFN-a that are typical of the illness. Interferon stimulated genes (ISGs) are more significantly expressed in the LCLs of AGS patients, as described in another study of ours (30) which also demonstrated the overexpression of the TLR9 gene. Moreover, although we are aware that the age difference between healthy controls and AGS patients, may be a limitation in the correlation, we also observed that the mtDNA copy number, but not the D-loop methylation levels, increased with increasing age at sampling in AGS patients but there was no correlation with sex.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Of possible relevance, we note that AGS has been suggested to involve a disturbance of mitochondria activity in some patients 46, 47 . Notably, a recent report revealed alteration of mitochondrial integrity associated with uncontrolled oxidative phosphorylation, increased ROS activity and mitochondrial stress in AGS patients mutated in RNASEH2A or RNASEH2B 48 . We propose here, that HIF-1εξ loss of activity could be a driver of mitochondrial dysfunction in AGS patients.…”
Section: Discussionmentioning
confidence: 99%